(untitled) (Journal of Hama University, 2019)
The aim of the study was to evaluate the retention of the pit and fissure sealant in Down syndrome patients. The sample consisted of 40 down syndrome patients. Pit and fissure sealant had been applicated for 20 patients using total etch bonding system and 20 patients using self-etch bonding system. The results showed significant differences (p≤0.05) in pit and fissure sealant retention which was higher in the total etch group in comparison to self-etch group in all study times. The study concluded that the retention of the pit and fissure sealant applicated with the traditional total-etch bonding system was higher than the retention of the self- etch bonding system.